A review of self-healing electrolyte and their applications in flexible/stretchable energy storage devices. (1st February 2022) - Liao, Haiyang; Zhong, Wenzhao; Li, Ting; Han, Jieling; Sun, Xiao; Tong, Xili; Zhang, Yongqi
Abstract: With the tremendous development of wearable electronics over the last decades, flexible/stretchable energy storage devices have gained growing attention. However, as a result of repetitive fatigue deformation accompanied by electrochemical depletion process, the electrolyte in these devices may sustain varying degrees of damage, including cracks, fissures, punctures, and encrustations, which can lead to serious performance degradation or even safety issues. Simultaneously, self-healing capacity, inspired by biological organs, has been identified to be a viable solution for addressing these issues by restoring mechanical and electrochemical performance. This review first outlines a full scheme for flexible/stretchable energy storage devices and the basic principle of self-healing. Then, we discuss the essential work of several self-healing electrolyte systems in energy storage devices. Finally, the crucial challenges and promises of future potential solutions for self-healing electrolytes, flexible/stretchable energy storage devices or even electronics are presented.